Fracture of the delivery balloon shaft during balloon‐expandable prosthesis alignment during implantation of an Edwards SAPIEN 3. Issue 5 (3rd May 2016) - Arai, Takahide; Hovasse, Thomas; Chevalier, Bernard
Abstract : The expandable sheath was designed with a lower profile in order to reduce the incidence of vascular complications of transcatheter aortic valve implantation using transfemoral approach. However, once the prosthesis has crossed the sheath, it could be difficult to retrieve it from the body. This is the first case of successful bail‐out in an instance of delivery balloon shaft malfunction subsequent to the crossing of an expandable sheath during implantation of an Edwards SAPIEN 3 prosthesis. © 2016 Wiley Periodicals, Inc.